Generalized Derivations and Generalized Jordan Derivations on C∗-Algebras through Zero Products - Abbas Zivari-Kazempour; Abasalt Bodaghi (Journal of Mathematics)
Let A be a unital C∗-algebra and X be a unitary Banach A-bimodule. In this paper, we characterize continuous generalized derivations and generalized Jordan derivations as form D:A⟶X through the action on zero product. In other words, we show that under some conditions on elements of A, a linear map on A can be a generalized Jordan derivation.